If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying p + -4q + 5p + -1q = 0 Reorder the terms: p + 5p + -4q + -1q = 0 Combine like terms: p + 5p = 6p 6p + -4q + -1q = 0 Combine like terms: -4q + -1q = -5q 6p + -5q = 0 Solving 6p + -5q = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '5q' to each side of the equation. 6p + -5q + 5q = 0 + 5q Combine like terms: -5q + 5q = 0 6p + 0 = 0 + 5q 6p = 0 + 5q Remove the zero: 6p = 5q Divide each side by '6'. p = 0.8333333333q Simplifying p = 0.8333333333q
| (x/-2)-12=15 | | log[4](x-3)+log[4](x-3)=1 | | 6x-20=2x+9 | | 6f+24= | | 9x-8xy= | | 1/3(15x-12)=9x-6 | | X+5.15=7.90 | | 2x-3x-7:4=x+1 | | 4x+2-2x=5x+2+4x | | 17+y=3x+25 | | 5x+10=-5-10 | | x^2+6y^2-600=0 | | (18x^4)/(25x^2 | | p(X)=1.50x-18 | | 6f-2=-14 | | 5x-4=9x-6 | | 8=3a+14 | | 6x+6+4x=12x+15-3x | | x-0.15x=3000 | | 3+8+x:2=2x+13 | | 3x=15/100 | | 6c+1=4c+9 | | 2.25x=0.9(x+3.3) | | 1.95+8.91= | | 3x+9+4x=9x+16-3x | | (4x-2)(-3x+2)= | | 2(5m+3)=46 | | 6x-6=4x+14 | | 6x-18-5x+15=5-x | | 2(25x-30)=3(12x+16) | | Y=1/4x^2-3 | | 10=2+4w |